Game Edukasi Deutsch Bilder untuk Penguasaan Kosakata Bahasa Jerman di SMA Negeri 6 Malang - Perdana, Syauqi Setya; Aini, Desti Nur (Singular: Journal of Pedagogical Language, Literature, and Cultural Studies, 2024)
The research aims to design and develop a German vocabulary learning application that can facilitate the learning process forstudents. The methodology used is Research and Development (R&D) by adopting the ADDIE research model, which includes thestages of analysis, design, development, implementation, and evaluation. The data collected comprises both qualitative andquantitative data through the distribution of questionnaires to the research subjects, which include 11th-grade languagestudents at SMAN 6 Malang, as well as material experts, media experts, and observers. The validation of the Deutsch Bildereducational vocabulary game application was conducted by media and material experts, resulting in an "A" rating, indicating theapplication's validity and feasibility as a supplementary medium for A1-level German language learning.